Effects of irrigation dams on riverine biota in mountain streams - Rocha Pompeu, Cássia; Peñas, Francisco J.; Barquín, José (Frontiers in Environmental Science, 2024)
Mountain streams harbor unique biodiversity and provide essential ecosystem services to human societies. Yet, these ecosystems face numerous threats, such as the construction of dams and land use changes, leading to rapid habitat degradation, water pollution, and biodiversity loss. In this study, we assess the effect of irrigation dams on mountain riverine biota using traditional biotic indices and trait-based approaches. We selected diatom and macroinvertebrate communities surveyed between 2015 and 2017 in mountain streams located in different regions in northern Spain (Cantabrian Cordillera, Iberian System, and Pyrenees) under natural and altered flow conditions (i.e., downstream of irrigation dams). Hydrological and biological changes related to the presence of dams, the mountain range, and the interaction between these two factors were identified. Summer flows, frequency of high flow events, and minimum annual flows timing were significantly affected by irrigation dams, independently of the region. Winter flows, the magnitude of high flow extremes, and the number of flow rises and falls varied significantly with the dam-mountain range interaction. The frequency and duration of flow pulses depended on the mountain range only. In the Cantabrian Cordillera, a region with larger reservoirs (>150 hm3), impacted sites showed a marked inversion of the seasonal flow patterns (i.e., increased summer flows but reduced winter flows). In the other mountain ranges, reservoirs had smaller storage volumes and multiple purposes, causing significant flow change frequency variations. Diatom traits, taxonomic richness, diversity, and IPS score varied with dam presence and mountain ranges, while macroinvertebrate traits and biotic indices responded weakly. These findings suggest that diatom communities might be more sensitive to hydrological alteration, while macroinvertebrates might be more influenced by space-related factors, such as biogeography and dispersal, overriding dam-related impacts. Furthermore, dam-related changes in ecosystems may depend not only on the presence of dams and their characteristics (e.g., reservoir size and operation), but also on local conditions and biogeography. Our findings emphasize that, when using pre-existing biomonitoring datasets, although some dam-related patterns emerge (e.g., with diatoms), other patterns may be constrained by the datasets’ low spatio-temporal coverage and taxonomic resolution, highlighting the need of well-structured study designs.